The MPATH-Dx reporting schema for melanocytic proliferations and melanoma - Piepkorn, Michael W.; Barnhill, Raymond L.; Elder, David E.; Knezevich, Stevan R.; Carney, Patricia A.; Reisch, Lisa M.; Elmore, Joann G. (Journal of the American Academy of Dermatology, 2014)
The histologic diagnosis of melanoma and nevi can be subject to discordance and errors, potentially leading to inappropriate treatment and harm. Diagnostic terminology is not standardized, creating confusion for providers and patients and challenges for investigators. We sought to describe the development of a pathology reporting form for more precise research on melanoma and a diagnostic-treatment mapping tool for improved patient care and consistency in treatment. Three dermatopathologists independently reviewed melanocytic lesions randomly selected from a dermatopathology database. Melanocytic Pathology Assessment Tool and Hierarchy for Diagnosis (MPATH-Dx) reporting schema evolved from iterative case review and form revision. Differences in diagnostic thresholds, interpretation, and nomenclature contributed to development of the MPATH-Dx histology reporting form, which groups lesions by similarities in histogenesis and degrees of atypia. Because preliminary results indicate greater agreement regarding suggested treatments than for specific diagnoses, the diverse terminologies of the MPATH-Dx histology reporting form were stratified by commonalities of treatments in the MPATH-Dx diagnostic-treatment mapping scheme. Without transformative advances in diagnostic paradigms, the interpretation of melanocytic lesions frequently remains subjective. The MPATH-Dx diagnostic-treatment mapping scheme could diminish confusion for those receiving reports by categorizing diverse nomenclature into a hierarchy stratified by suggested management interventions.